1993
DOI: 10.1128/jcm.31.11.2952-2959.1993
|View full text |Cite
|
Sign up to set email alerts
|

Role of specific immunoglobulin E in diagnosis of acute toxoplasma infection and toxoplasmosis

Abstract: Toxoplasma immunoglobulin E (IgE) antibodies were evaluated in an immunosorbent agglutination assay (ISAGA) and an enzyme-linked immunosorbent assay (ELISA) to determine their usefulness in the diagnosis of acute infection with Toxoplasma gondii. IgE antibodies were not detected in serum specimens from otherwise seronegative individuals, individuals with chronic toxoplasma infection, or infants without congenital toxoplasmosis. In contrast, they were detected in pregnant women who seroconverted during gestatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
32
6
6

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(47 citation statements)
references
References 16 publications
3
32
6
6
Order By: Relevance
“…IgA known for its role in neutralization of toxins and pathogenic microbes, (29,30), while IgM had been associated with neutrophils phagocytic activity and complement cascade activation, which might result in killing of the T. gondii parasite (31,32). In this study, no significant change in IgE was observed after vaccination with TgMDH, although previous investigations showed the existence of this antibody during diagnosis of T. gondii infection (33,34).…”
Section: Discussioncontrasting
confidence: 66%
“…IgA known for its role in neutralization of toxins and pathogenic microbes, (29,30), while IgM had been associated with neutrophils phagocytic activity and complement cascade activation, which might result in killing of the T. gondii parasite (31,32). In this study, no significant change in IgE was observed after vaccination with TgMDH, although previous investigations showed the existence of this antibody during diagnosis of T. gondii infection (33,34).…”
Section: Discussioncontrasting
confidence: 66%
“…IgE ELISA shows lower sensitivity than IgM assays [29][30][31], but the present study shows that, as with IgA, decreased sensitivity is not necessarily caused by failure to form these antibodies, and can also be caused by delayed or early cessation of antibody production, resulting in IgE antibodies being undetected during sample collection. Of all the antibody classes, IgE has the shortest duration, with positive results for up to 6 months following onset of symptoms, but this period can vary from 3 -5 months to 11 months [31][32][33][34]. Foudrinier et al [30] described two different kinetic patterns in asymptomatic seroconverters (short duration) and in seroconverters with overt toxoplasmosis, in which high IgE levels persist for a number of months.…”
contrasting
confidence: 57%
“…PAMF serological tests. The Sabin-Feldman dye test (14), direct agglutination test (6), double-sandwich IgM ELISA (10), IgA ELISA (15), IgE ISAGA (18), IgE ELISA (18), and AC/HS (4) were performed as previously described. The Sabin-Feldman dye test is considered the "gold standard" for detection of IgG antibodies against T. gondii.…”
Section: Methodsmentioning
confidence: 99%
“…Comparisons were performed both retrospectively on selected sera that had previously been tested in our laboratory and prospectively on consecutive sera from adults that had been received by our laboratory for diagnostic testing. In order to investigate the significance of detection of IgM antibodies by either method, results obtained in additional serological tests, including IgA (15) and IgE ELISAs (18), IgE immunosorbent agglutination assay (ISAGA) (18), and differential agglutination (AC/HS) tests (4), as well as results of follow-up serological tests, were analyzed.…”
mentioning
confidence: 99%